Brain Drain [Propensity for Malaysian Professionals to Leave for Singapore] - Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul (Springer, 2016)
The increase in the movement of populaces around the globe transcending physical, national, social frontiers and most common migration trend is when migrants move to advanced nations from the lesser developed nations. The first gives the general idea of the research of the study. This chapter brings forth the problem statement, research objectives and questions and some of key terms definitions.